Medication overuse headache: a review of current evidence and management strategies - Kebede, Yabets Tesfaye; Mohammed, Bekri Delil; Tamene, Beimnet Ayenew; Abebe, Abel Tezera; Dhugasa, Rabbi Waqshum (Frontiers in Pain Research, 2023)
The third edition of the International Classification of Headache Disorders (ICHD-3) defines medication-overuse headache (MOH) as a headache that develops when a person regularly uses acute or symptomatic headache medications excessively (10 or more, or 15 or more days per month, depending on the medication) for a period of time longer than 3 months. Even though it may not be reported as frequently as it actually is, it affects about 5% of the general population on average. It typically happens following repeated anti-pain medication use for pre-existing headache disorders, such as migraines. Anti-pains can also be used frequently in patients with pre-existing headache disorders for reasons other than treating headaches, such as psychological drug attachment. MOH is linked to a number of illnesses, such as anxiety, depression, and obsessive compulsive disorder (OCD). Both simple and complex types are possible. Additionally, there is no universal consensus on how to treat MOH, but drug discontinuation is the best course of action. Using the medical subject headings “Medication Overuse Headache,” “Migraine Headache,” “Tension Headache,” “Chronification of Headache,” and “Antipains,” an all-language literature search was done on PubMed, Google Scholar, and Medline up until March 2023. We looked into the epidemiology, risk factors, pathophysiology, clinical characteristics, comorbidities, diagnosis, management, and preventative measures of MOH in the literature. This article focuses on the MOH research themes.